The Role of Green Bonds in Financing Sustainable Energy Projects: Trends and Prospect - Ozyesil, Mustafa; Tembelo, Havane (International Journal of Energy Economics and Policy, 2025)
This study investigates the determinants of green bond issuance across multiple countries from 2017 to 2023, with a panel data analysis approach. The analysis focuses on the impact of interest rates, renewable energy capacity, carbon emission reduction, and GDP on green bond issuance. To determine the long-run equilibrium relationship among these variables, the Pedroni co-integration test was employed. The results confirmed the presence of co- integration, validating the use of Panel Dynamic OLS (DOLS) for estimating the long-run coefficients. DOLS, which includes leads and lags of the differenced independent variables, were utilized to account for potential endogeneity and serial correlation, providing robust estimates. The findings indicate that higher interest rates are associated with lower green bond issuance, while greater renewable energy capacity and higher GDP positively correlated with increased green bond issuance. Carbon emission reduction shows a negative relationship, suggesting a saturation effect in countries with significant existing reductions.